Lessons learnt from promising practices in community engagement for the elimination of new HIV infections in children by 2015 and keeping their mothers alive: summary of a desk review - Laurie Gulaid; Karusa Kiragu (2012)
Introduction Through The Global Plan Towards the Elimination of New HIV Infections Among Children by 2015 and Keeping their Mothers Alive , leaders have called for broader action to strengthen the involvement of communities. The Global Plan aspires to reduce new HIV infections among children by 90 percent, and to reduce AIDS‐related maternal mortality by half. This article summarizes the results of a review commissioned by UNAIDS to help inform stakeholders on promising practices in community engagement to accelerate progress towards these ambitious goals. Methods This research involved extensive literature review and key informant interviews. Community engagement was defined to include participation, mobilization and empowerment while excluding activities that involve communities solely as service recipients. A promising practice was defined as one for which there is documented evidence of its effectiveness in achieving intended results and some indication of replicability, scale up and/or sustainability. Results Promising practices that increased the supply of preventing mother‐to‐child transmission (PMTCT) services included extending community cadres, strengthening linkages with community‐ and faith‐based organizations and civic participation in programme monitoring. Practices to improve demand for PMTCT included community‐led social and behaviour change communication, peer support and participative approaches to generate local solutions. Practices to create an enabling environment included community activism and government leadership for greater involvement of communities. Committed leadership at all levels, facility, community, district and national, is crucial to success. Genuine community engagement requires a rights‐based, capacity‐building approach and sustained financial and technical investment. Participative formative research is a first step in building community capacity and helps to ensure programme relevance. Building on existing structures, rather than working in parallel to them, improves programme efficiency, effectiveness and sustainability. Monitoring, innovation and information sharing are critical to scale up. Conclusions Ten recommendations on community engagement are offered for ending vertical transmission and enhancing the health of mothers and families: (1) expand the frontline health workforce, (2) increase engagement with community‐ and faith‐based organizations, (3) engage communities in programme monitoring and accountability, (4) promote community‐driven social and behaviour change communication including grassroots campaigns and dialogues, (5) expand peer support, (6) empower communities to address programme barriers, (7) support community activism for political commitment, (8) share tools for community engagement, (9) develop better indicators for community involvement and (10) conduct cost analyses of various community engagement strategies. As programmes expand, care should be taken to support and not to undermine work that communities are already doing, but rather to actively identify and build on such efforts.